DILEMATIKA PENEGAKAN HUKUM TERHADAP PENYELESAIAN SENGKETA PEMILIHAN KEPALA DESA DI INDONESIA - Siti Mariyam; Adhi Putra Satria (Faculty of Law - Tarumanagara University, 2020)
This study aims to find out and analyze how the settlement of disputes over the election results of village heads in Indonesia, after the birth of Law No. 6 of 2014 on Villages, as well as how the legal problems that arise from the existence of these regulations. This research is a normative juridical study with the main data used in the form of secondary data, while the approach taken is to use an approach to the laws and regulations (Statute approaches). The results showed that the disputes over the results of village head elections in Indonesia at this time, experienced a development and legal problems in its enforcement. The problem referred to is that when Law No. 6 of 2014 gave the Regent / Mayor authority in resolving disputes over the results of village head elections, with this fact, several legal problems arose, especially when the Regent / Mayor was a state institution whose main task was not to enforce the law, and the handling of the settlement will be difficult to be objective because there will be mixed political responsibilities in the settlement process